The Effect of Political Risk and Economic Stability on Foreign Direct Investment Flows in Asean-6 - Irtifa Umi Azizah; Muhammad Aswad; Rokhmat Subagiyo (Ecoplan, 2025)
This study analyzes the influence of political risk and economic stability on Foreign Direct Investment (FDI) inflows in six ASEAN countries (Indonesia, Malaysia, Singapore, the Philippines, Thailand, and Vietnam) during the period 2013–2023. A quantitative approach with a panel data regression method was employed, where the dependent variable is FDI inflows (in million USD), while the independent variables consist of control of corruption as an indicator of political risk, and GDP and inflation as indicators of economic stability. Data were obtained from the World Bank, IMF, and Worldwide Governance Indicators (WGI). The regression model was selected based on the Chow and Hausman tests, and the analysis was conducted using EViews software. The results show that control of corruption has a positive and significant effect on FDI, emphasizing the importance of good governance and anti-corruption efforts in building investor confidence. GDP also has a positive and significant effect on FDI, reflecting the role of strong economic growth as a major attraction for foreign investors. Meanwhile, inflation has no significant effect on FDI, indicating that investors tend to prioritize factors such as policy stability, infrastructure quality, and institutional effectiveness over short-term price fluctuations. From a policy perspective, the findings suggest that ASEAN countries should strengthen governance quality and foster a transparent investment environment free from corruption to enhance foreign capital inflows. In addition, governments need to maintain macroeconomic stability through effective fiscal and monetary coordination while improving infrastructure and human capital development to attract sustainable long-term investments.